Strategic Organizational Capability for Mobile Banking Service Recovery in The Banking Industry: A Systematic Literature Review - Dian Sari Iriani; Munawar Asikin (Riviera Publishing, 2026)
Purpose – The rapid digital transformation of the banking industry has significantly increased customer reliance on mobile banking services while simultaneously exposing banks to increasingly complex digital service failures. Although previous studies have extensively examined customer satisfaction, service quality, trust restoration, perceived justice, and loyalty following service recovery, limited attention has been given to the organizational capabilities that enable banks to effectively manage mobile banking service recovery. This study aimed to develop a conceptual framework of Strategic Organizational Capability (SOC) by systematically synthesizing literature on service recovery, service marketing, Service-Dominant Logic, and Dynamic Capability Theory within the banking industry context. Design/Methodology/Approach – This study employed a Systematic Literature Review (SLR) using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) framework as the review protocol. Relevant studies were identified from major international academic databases and analyzed using a concept-centric thematic synthesis approach. The review integrated complementary theoretical perspectives to identify organizational capability dimensions that supported effective mobile banking service recovery. Findings – The synthesis identified six interrelated organizational capability dimensions: Strategic Leadership, Organizational Governance, Digital Infrastructure Capability, Cross-functional Integration, Organizational Learning, and Customer Recovery Management. These dimensions collectively formed Strategic Organizational Capability, conceptualized as a higher-order organizational capability that enabled banks to anticipate, coordinate, manage, recover from, and continuously learn from mobile banking service failures while maintaining customer trust and supporting long-term value co-creation.